Oral Candida Overgrowth in most Thalassemia Major Patients, Yeast Identification by CDA, VITEK 2, and PCR, and Evaluating their Virulence Factors in Thi-Qar, Iraq: Pertumbuhan Candida Oral yang Berlebih pada Sebagian Besar Pasien Thalassemia Mayor, Identifikasi Ragi dengan CDA, VITEK 2, dan PCR, dan Evaluasi Faktor Virulensinya di Thi-Qar, Irak - Jabbar, Salih; Jafar, Furdos Nouri; Al-Ali, Shereen; Hameed, Afaq (Indonesian Journal on Health Science and Medicine, 2025)
Candida, an opportunistic fungus in immunocompromised patients, can cause an infection like oral candidiasis which usually starts with Candida overgrowth. Thalassemia major (TM) patients are known to suffer from immune abnormalities that may lead to a condition of immune deficiency. So, we aimed to estimate the prevalence and intensity of Candida growth in oral cavity of TM patients, determine the accuracy of Candida identification, and assess some virulence factors. Our study was conducted on 150 TM patients and 80 controls between (1-40 years). Oral swabs were used for microscopic examination and culturing on SDA. The identification was done by candida differential agar (CDA), VITEK 2, and conventional PCR. Also, the virulence was estimated by measurement of proteinase, phospholipase, lipase, hemolysin, and biofilm. Candida species were orally isolated from 70% of TM patients with mean colony count (124±94) significantly more than 42.5% of control with (11±7), so a significant oral Candida overgrowth was observed in most (TM) patients compared with the control, referring to an increased probability of developing to oral candidiasis. Significantly, in total TM patients, male or female patients, the age group (11–20) showed a higher prevalence of Candida than other age groups, at 52.4%, 49%, and 55.56%, respectively. PCR identified 105 isolates from TM patients: C. albicans constituted the most common species with (61.9%), C. dubliniensis (35.2%) and C. glabrata (2.86%). Generally, in comparison with results of PCR, the accuracy of identification by CDA was (95.2%) more than (87.6%) by VITEK 2, but both were typical methods for identifying C. albicans with (100%). Significantly, the higher production of proteinase and lipase was by (92.3%) and (90.7%) of C. albicans isolates, respectively. While the majority of phospholipase and biofilm production was noted by (70.3%) of C. dubliniensis and (100%) of C. glabrata, respectively. All Candida species were hemolysin producers with 100%. Highlights: Samples: 150 TM patients, 80 controls; oral Candida prevalence 70%. Identification: PCR, CDA, VITEK 2; C. albicans most common (61.9%). Virulence: High proteinase, lipase (C. albicans); biofilm (C. glabrata). Keywords: accuracy of Candida identification, biofilm, extracellular enzymes, oral Candida overgrowth, thalassemia major patients